Effect of packaging and aging time on shelf-life of beef meat - A. Ficco; F. Signorelli; M. Contò; M. Iacurto; S. Failla; S. Ballico (Italian Journal of Animal Science, 2010)
The present study aimed to determinate beef meat shelf-life packaged in modified atmosphere (MAP). The experiment was carried out on young bulls Longissimus dorsii muscle and considered 2 thesis (meat portioned and conserved in MAP after 3 days “NA” and after 7 days “7A” of ageing), 2 types of packaging (with or without water absorbent pad) and 3 different conservation times (3, 7 or 11 days). The analysis regarded: water loss, colour, TBArs and protein ossidation. Liquid loss showed higher value in packaged meat with absorbent pad than the other (10.38% vs 2.42% P<0.001), while the evaporate liquid was highest in no absorbent pad samples. The positive effect of pad was found in metmyoglobin percentage (13.98 vs 15.10 % respectively for its presence and absence) and protein oxidation (67.32 vs 79.26 nmol thiol/mg protein P<0.05). TBArs increased with conservation times from 0.88 to 2.57 mg/100g, while it didn’t show differences between the two thesis and the two different packaging methods. In conclusion the use of absorbent pad improved meat nutritive quality despite produced more water loss.